Effects of polyethylene glycol stress on ion contents in nutritive organs of alfalfa seedlings - LI Bo; XU Wanyu; SHI Shanliang (浙江大学学报. 农业与生命科学版, 2017)
The ions distribution in plants was changed under drought and other stresses. Plants could alleviate the damages caused by drought and enhance the adaptability to drought by re-constructing a new balance of sodium (Na+), potassium (K+), calcium (Ca2+) and magnesium (Mg2+) ions. Alfalfa, a kind of perennial leguminous plant, is the best and most important leguminous grass in the world. It plays important roles in the development of animal husbandry and the improvement of agricultural ecological environment. However, the development of alfalfa industry is limited because of the drought in the main planting area for alfalfa in North China. Monitoring the distribution changes of the four ions in drought-resistant and drought-sensitive alfalfa under drought stress would help to understand the mechanism by which alfalfa resists drought stress.Water culture method was used to examine the contents changes of Na+, K+, Ca2+, Mg2+ in different organs of alfalfa cultivars Grassland 1 (drought-resistant) and Longmu 81 (drought-sensitive) under different concentrations 10%,15%,20%,25% of polyethylene glycol (PEG) stress (simulating drought stress), to investigate the responses of alfalfa to drought stress regarding to ions balance.The results showed that in both drought-resistant and drought-sensitive alfalfa seedlings, the content of Na+ increased whereas the contents of K+, Ca2+ and Mg2+ decreased in the roots, stems and leaves with the increase of PEG concentration. In the same condition, the ratios of K+ to Na+ (K+/Na+), Ca2+ to Na+ (Ca2+/Na+) and Mg2+ to Na+ (Mg2+/Na+) were decreased or decreased at first and then increased.The increment of Na+ content in the roots of Grassland 1 was more than that of Longmu 81 under low concentration of PEG stress, and the same phenomenon was observed in leaves under high concentration of PEG. Besides, it was opposite in other organs under different concentrations of PEG stress. Under high concentration of PEG, the increments of K+ and Mg2+ contents in the roots and leaves of the Grassland 1 were more than those of Longmu 81, whereas they were less in the stems. The increment of Ca2+ content in roots, stems and leaves of the Grassland 1 were all significantly more than those of Longmu 81 under different concentrations of PEG, respectively. Compared with Longmu 81, the ratios of K+/Na+, Ca2+/Na+, Mg2+/Na+ in roots and leaves, and the ratio of Ca2+/Na+ in Grassland 1 were all increased under high concentration of PEG.With the increase of PEG concentration, in the roots, stems and leaves of alfalfa seedlings, Na+ content increased whereas K+, Ca2+, Mg2+ contents decreased, and the ratios of K+/Na+, Ca2+/Na+, Mg2+/Na+ decreased too. When the concentration of PEG was 25%, the contents of K+, Ca2+, Mg2+ and the ratios of K+/Na+, Ca2+/Na+, Mg2+/Na+ in the roots and leaves of drought-resistant alfalfa (Grassland 1) were more than those of drought-sensitive one (Longmu 81), but it was not the case in stems. These suggested that the changes of ion content may be involved in the drought resistance of alfalfa.